Awareness and Adoption of Improved Sericulture Technologies - N.Sakthivel; P. Kumaresan; R. Balakrishna; B.Mohan (Journal of Agricultural Extension Management, 2025)
The paper attempts to analyze the awareness and adoption pattern of sericultural practices by the farmers of Thirunelveli and Virudunagar districts in Southern Tamil Nadu. The adoption rate was good for plant spacing, weed management, irrigation and leaf/shoot harvesting with respect to mulberry cultivation technology. In case of silkworm rearing, the adoption rate was very good with simple technologies such as bed spacing, shoot rearing, ventilation, moulting care, harvesting of cocoon, transportation of cocoon etc. On the other hand, the rate of adoption was less or partial with respect to application of fertilizers, rearing silkworm in separate rearing house, disinfection of rearing house and appliances, maintenance of rearing hygiene and integrated pest management practices : The correlation  analysis showed that extension contact and training programmes played . An important role in educating the farmers to adopt improved technologies.